2007
DOI: 10.1002/chin.200715275
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Modulating the Biological Effects of Peroxynitrite and Related Nitrogen Species

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Finally, a similar study in lung epithelium showed that ONOO Ϫ -induced NT colocalized with F-actin and resulted in actin depolymerization (28). We therefore hypothesize that nitrosylation is a mechanism causing disruption of the normal state of F-actin, resulting in depolymerization, possibly through structural/conformational changes to actin (44,52).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Finally, a similar study in lung epithelium showed that ONOO Ϫ -induced NT colocalized with F-actin and resulted in actin depolymerization (28). We therefore hypothesize that nitrosylation is a mechanism causing disruption of the normal state of F-actin, resulting in depolymerization, possibly through structural/conformational changes to actin (44,52).…”
Section: Discussionmentioning
confidence: 70%
“…Whether this is due to apoptosis or cell damage not related to apoptosis is also unclear. We have hypothesized that nitrosylation interferes with the normal state of F-actin resulting in depolymerization, possibly through structural changes to actin (44,52). In support of this, others have shown that nitrosylation can be a form of posttranslational protein modification resulting in targeting and accelerated degradation of proteins by activated peroxisomes (50).…”
Section: Discussionmentioning
confidence: 97%
“…As Scheme 1 shows, LA is reduced to form DHLA by NaBH 4 . In this work, the antioxidant abilities of LA and DHLA are compared by interacting with peroxynitrite (ONOO − ) [10], galvinoxyl radical, 2,2 -azinobis(3-ethylbenzothiazoline-6-sulfonate) cation radical (ABTS +• ), 2,2 -diphenyl-1-picrylhydrazyl (DPPH), and linoleic acid (LH)-β-carotene emulsion. Then, LA and DHLA are applied to protect linoleic acid (LH) against 2,2 -azobis(2-amidinopropane hydrochloride) (AAPH)-induced oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of CO 2 Peroxynitrite is implicated in several physiological and pathological events, including cell signaling, drug metabolism, microbial pathogenesis, atherosclerosis, inflammation, and neurodegenerative disorders. It reacts with various bio-molecules including proteins, lipids, and DNA by either direct reaction with a target molecule or immediately after homolysis to Å NO 2 and hydroxyl radical ( Å OH) or after reaction with CO 2 and homolysis to CO 3 ÅÀ and Å NO 2 [1][2][3][4][5][6][7][8][9][10][11]. Besides their role in O 2 transport and storage, globins also catalyze several reactions aimed to scavenge toxic reactive nitrogen and oxygen species.…”
mentioning
confidence: 99%